2019
DOI: 10.1038/s41467-019-11378-4
|View full text |Cite
|
Sign up to set email alerts
|

The Eleanor ncRNAs activate the topological domain of the ESR1 locus to balance against apoptosis

Abstract: MCF7 cells acquire estrogen-independent proliferation after long-term estrogen deprivation (LTED), which recapitulates endocrine therapy resistance. LTED cells can become primed for apoptosis, but the underlying mechanism is largely unknown. We previously reported that Eleanor non-coding RNAs (ncRNAs) upregulate the ESR1 gene in LTED cells. Here, we show that Eleanors delineate the topologically associating domain (TAD) of the ESR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…Suppression of Eleanor RNAs reduces the ESR1 transcription. Therefore, Eleanors may be a good therapeutic target for breast cancers 25,43,44 . However, the mechanism by which Eleanor RNAs stimulate the ESR1 transcription has remained enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of Eleanor RNAs reduces the ESR1 transcription. Therefore, Eleanors may be a good therapeutic target for breast cancers 25,43,44 . However, the mechanism by which Eleanor RNAs stimulate the ESR1 transcription has remained enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…ELEANORS also play a role in mediating long-range chromatin interactions and balancing between cell proliferation and apoptosis. 64…”
Section: Aberrant Nuclear Microenvironment Is Created Through Llps mentioning
confidence: 99%
“…Therefore, u-Eleanor may be used as a biomarker of breast cancer at early stages [116]. Furthermore, a recent study has revealed the function of another Eleanor called promoter-associated Eleanor (pa-Eleanor), which is transcribed from the region proximal to the transcriptional start site of ESR1 [120]. In the nucleus, chromosomes fold into domains called topologically associating domains (TADs), which exhibit intra-chromatin interactions [121].…”
Section: Lncrnas Belonging To Multiple Categoriesmentioning
confidence: 99%